PENGARUH USABILITY TERHADAP KEPUASAN PENGGUNA PADA E-CAMPUS UNIVERSITAS NAHDLATUL ULAMA INDONESIA (UNUSIA) - Reza Fahlevi, Mohammad (Pusat Riset dan Inovasi Nasional, 2022)
The E-Campus system is a website-based application to manage academic activities at an educational institution. Nahdlatul Ulama University of Indonesia (UNUSIA) is one of the educational institutions that has implemented this system to support the learning process for students, lecturers, and teaching staffs. The UNUSIA E-Campus system (https://ecampus.unusia.ac.id) has an important role in the teaching and learning process, especially during the current pandemic. The system must be of high quality to ensure that services and information provided are in accordance with users needs and to measure users satisfaction by assessing the quality of the system from different variables. The measurement of users satisfaction is influenced by the usability of the UNUSIA E-Campus system. Usability is done to measure user satisfaction by assessing the quality of the system from various variables. This research was conducted by distributing questionnaires to students, lecturers, and teaching staff in UNUSIA. The results showed that content, accuracy, format, ease of use, and timeliness on the usability of the system had a significant effect on user satisfaction at the UNUSIA E-Campus. Keywords: E-Campus, UNUSIA, users satisfaction, usability.